The constant and continuous voice of workers in Argentina - Atzeni, Maurizio (2016)
It could be argued that in Argentina, workers’ voice has never been silenced. In a legislative system protecting workers and politically and legally empowering trade unions, these organisations have historically represented workers. Voice however has never been limited to institutionalised and organisational forms. It has often exploded in informal ways out of workers’ experiences of the precariousness of their labour processes and of the contradictions generated between this and formal voice and representation. But it has also emerged in novel forms, through the occupation of factories, roads and public places, in moments of deep economic crisis or among groups of informally employed workers. The case of Argentina certainly calls for a broader understanding of voice tied to the idea of voice as a socially and politically mediated process, through which formal and informal channels of voice can be alternatively created, destroyed and recreated.